Sanksi Pidana dalam Pengalihan Fungsi Ruang Terbuka Hijau - Zam Zam Mutiara Aulia; Moh. Bagus; Arief Firmansyah (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2023)
Research with the title "Criminal Sanctions in the Transfer of Functions of Green Open Spaces" is an abstraction of the problems of transferring functions of green open spaces. This study aims to answer the case of the transfer of the function of RTH (Green Open Space) which has been carried out by the management of RW (Rukun Tetangga) Citra Sentosa Mandiri Housing Complex located in Sidoarjo district. The transfer of function of the Green Open Space to utilize the Green Open Space as a place to sell street vendors provided for the housing residents themselves. In this study, the authors used normative research methods, which are scientific research procedures to find truth based on scientific logic from a normative perspective. This research is basically based on a critical and in-depth study of literature and legal documents that are relevant to the legal issues studied. The results of the research that the author has reviewed using normative research methods show that the RW (Rukun Warga) Citra Sentosa Mandiri Housing Management has transferred functions that are not in accordance with applicable laws and received criminal sanctions in accordance with laws.